PERAN PROMOSI SEBAGAI VARIABEL INTERVENING PADA KEPUTUSAN PEMBELIAN PENGGUNA OPPO SMARTPHONE - Panjaitan, Feliks A.B.K.; Panjaitan, Hotman (JEM17: Jurnal Ekonomi Manajemen, 2021)
This study aims to find clarity about the role of promotion as a mediating variable on the relationship between product quality and price perception with purchasing decisions, by designing and forming a research model. This research approach is quantitative, explanatory. The population in this study were users of oppo smartphones in Surabaya. The research sample was 150 respondents who were determined using the non-probability method and purposive sampling. The analysis technique uses SEM Pls. The results showed that the research model was accepted with a Q-Square value of 0.573. This study also shows clarity that: product quality has no effect on promotion. Perception of price has an effect on promotion, and promotion has an effect on purchasing decisions. The results also explain that: the promotion variable acts as a positive mediation on the relationship between product quality and price perception with purchasing decisions.